2009
DOI: 10.1038/nsmb.1708
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal association of condensin II is regulated by a noncatalytic function of PP2A

Abstract: Mitotic chromosomal assembly in vertebrates is regulated by condensin I and condensin II, which work cooperatively but have different chromosomal localization profiles and make distinct mechanistic contributions to this process. We show here that protein phosphatase 2A (PP2A), which interacts with condensin II but not condensin I, plays an essential role in targeting condensin II to chromosomes. Unexpectedly, our data indicate that PP2A acts as a recruiter protein rather than a catalytic enzyme to target conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 48 publications
11
36
0
Order By: Relevance
“…40 PP2A has also been shown to be involved in recruiting KIF4 onto mitotic chromosome arms. 9 Interestingly, PRC1, the protein regulator of cytokinesis and a KIF4 interacting protein, has been found to interact with HSF2 at the hsp70i promoter. 41 The binding of KIF4 to heat shock elements (HSE) in vitro ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…40 PP2A has also been shown to be involved in recruiting KIF4 onto mitotic chromosome arms. 9 Interestingly, PRC1, the protein regulator of cytokinesis and a KIF4 interacting protein, has been found to interact with HSF2 at the hsp70i promoter. 41 The binding of KIF4 to heat shock elements (HSE) in vitro ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, KIF4, PARP1 and condensin have all been shown to interact with each other 38 and interactions between condensin, KIF4 and PARP-1 10,18,38 may act in concert in chromosome structure maintenance and genome integrity. 9 Importantly, PARP-1 also interacts with condensins 38 and has recently been implicated in homologous recombination on damaged DNA. 9,39 Furthermore, the interaction between condensin and PARP-1 is particularly strong during S phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the molecular details of how chromosome compaction is achieved during cell division are not clear. Recently, Takemoto et al (32) reported that PP2A interacts with condensin II but not condensin I and plays an essential role in targeting condensin II to chromosome. PP2A acts as a recruiter protein in the noncatalytic regulation, which is required for the chromosomal association of condensin II in human cells.…”
Section: Discussionmentioning
confidence: 99%